Study of Temperature Effect on Luminous Flux of High Power Chip on Board Light Emitting Diode - Quan, Cao Xuan; Xuan, Vu Khanh; Lan Anh, Luu Thi; Son, Vo Thach (Communications in Physics, 2014)
High power chip on board light emitting diode (HPCOBLED) are a promising solid state light technology for a variety of lighting applications. In this study, we studied temperature effect on luminous flux of HPCOBLED using VMI-PR-001 system of Vietnam Metrology Institute. The results according to the temperature Tc is increasing, luminous flux reduced. Especially HPCOBLED is larger power, decreasing luminous flux is larger. Reason of this is chance power. HPCOBLED model describes the temperature affection on luminous flux of HPCOBLED. The results of HPCOBLED model matched with that measured by the luminous flux measurement system (VMI-PR-001, Vietnam).